Determination of body segment inertia parameters using 3d human body scanner and 3D-CAD-software - Abe, T.; Yokozawa, T.; Takamatsu, J.; Enomoto, Y.; Okada, H. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
In the field of sports biomechanics, a human body is often treated as a linkage model to investigate various kinds of human movement. This modeling requires body segment inertia parameters (BSPs) such as masses, centers of mass, and moments of inertia. As the quality of motion capture system increases, more accurate BSPs are also needed to get accurate inverse dynamics results. Advanced technology has enabled us to obtain three-dimensional coordinates of the entire body surface. A 3D CAD software has also been able to be applied to measure the human body. It was hypothesized that BSPs with high accuracy could be determined by the combination of a 3D body scanner and a 3D CAD software. The purposes of this study are, first, to introduce a new method of measuring subject-specific BSPs and, second, to compare the BSPs from this study with those from an existing mathematical model in order to show that the proposed method can be used to produce more accurate BSPs.